Is aripiprazole similar to quetiapine for treatment of bipolar depression? Results from meta-analysis of Chinese data - Tao, Hejian; Wang, Jiawei; Shen, Dong; Sun, Fengli; Jin, Weidong (Frontiers in Psychiatry, 2022)
Objective To study the similarity and difference in clinical efficacy of aripiprazole and quetiapine in Chinese patients with bipolar depression by meta-analysis. Also to provide the evidence of aripiprazole in treatment for bipolar depression. Methods We searched Chinese literature related to the study in aripiprazole and quetiapine in treatment for bipolar depression ,among which results such as comments, letters, reviews and case reports were excluded. The clinical efficacy between aripiprazole and quetiapine was synthesized and discussed. Result A total of 1546 subjects were included in 17 studies. Random effect model is used to account for the data by Revman 5.2. The results showed that there was no significant difference in the remission rate between patients treated with aripiprazole and quetiapine as the scale evaluates the patients in the treatment of bipolar depression(221/501 vs 193/501,Z=1.12,P=0.26).But the results also showed that remission rate of aripripazole with lithium carbonate was significant higher than quetiapine with lithium carbonate in the treatment of bipolar depression(111/232 vs 69/232,Z=3.92,P<0.0001).The results showed that effective rate of aripripazole was similar to quetiapine in the treatment of bipolar depression(426/572 vs 386/572,Z=2.70,P=0.007).Overall there were no difference in HAMD score between patients treated with aripripazole and quetiapine(Z=1.68,P=0.09). The results also show that drop out rate of aripripazole was similar quetiapine in treatment bipolar depressive patients(Z=1.80,P=0.07). Conclusion As atypical antipsychotic, aripirazole maybe similar to quetiapine in treatment for bipolar depression with similar drop-out rate and higher remission rate in case of combination with lithium caebonate.But it is more cautious and careful to pay attention to these result due to lower quality of collected lecture.